Computer aided facial prosthetics manufacturing system - Heah, Kok Peng; Salleh, Mohamed Najib (2015)
Some people have facial deformities or disfigurement.There are many solutions for facial deformities like plastic surgery and facial prosthetics.Fabrication of a facial prosthetics using traditional manufacturing method is high cost, time consuming, and need of expertise. This study aimed to investigate a new method to develop a customized facial prosthetic.A 3D scanner, computer software and 3D printer were used in this study to investigate a new manufacturing method to develop the facial prosthetics.Results showed that the new developed method can be used to produce a customized facial prosthetics.The advantages of the developed method over the conventional process to fabricate facial prosthetic are low cost, reduce waste of material and pollution in order to meet the green concept.